Paraneoplastic syndromes in olfactory neuroblastoma - Kunc, Michał; Gabrych, Anna; Czapiewski, Piotr; Sworczak, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2015)
Olfactory neuroblastoma (ONB) is a raremalignant neoplasm of sinonasal tract, derived from olfactory epithelium. Unilateral nasal obstruction, epistaxis, sinusitis, and headaches are common symptoms. Olfactory neuroblastoma shows neuroendocrine differentiation and similarly to other neuroendocrine tumors can produce several types of peptic substances and hormones. Excess production of these substances can be responsible for different types of endocrinological paraneoplastic syndromes (PNS). Moreover, besides endocrinological, in ONB may also occur neurological PNS, caused by immune cross-reactivity between tumor and normal host tissues in the nervous system. Paraneoplastic syndromes in ONB include: syndrome of inappropriate ADH secretion (SIADH), ectopic ACTH syndrome (EAS), humoral hypercalcemia of malignancy (HHM), hypertension due to catecholamine secretion by tumor, opsoclonus-myoclonus-ataxia (OMA) and paraneoplastic cerebellar degeneration. Paraneoplastic syndromes in ONB tend to have atypical features, therefore diagnosis may be difficult. In this review, we described initial symptoms, patterns of presentation, treatment and outcome of paraneoplastic syndromes in ONB, reported in the literature.